The Influence of Organizational Culture and Motivation on Organizational Citizenship Behavior for the Environment (OCBE) with Job Satisfaction as Mediation (Case Study at PT. Dana Purna Investama) - Devita Chairunnisha; Setyo Riyanto (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Facility management services have experienced growth in Indonesia from 2022 to 2027, driven by the expansion of the construction sector. Within the sustainability concept, environmental crises have become a critical issue, necessitating eco-friendly behaviors in industrial and service organizations. PT. Dana Purna Investama (DPI) operates in the Facility Management Services sector, supported by competent human resources specializing in this field. This study aims to examine the effect of organizational culture and motivation on OCBE, mediated by job satisfaction. OCBE refers to voluntary pro-environmental behaviors exhibited by employees in the workplace. A purposive sampling technique was employed to select a sample of 125 employees. Data processing using SEM-PLS resulted in the following findings: (1) Organizational culture positively and significantly influences OCBE; (2) Motivation positively and significantly influences OCBE; (3) Job satisfaction positively and significantly influences OCBE; (4) Organizational culture positively and significantly influences job satisfaction; (5) Motivation positively and significantly influences job satisfaction; (6) Organizational culture positively and significantly influences OCBE, mediated by job satisfaction; (7) Motivation positively and significantly influences OCBE, mediated by job satisfaction.